Plan anual de contrataciones y la eficiencia en las adquisiciones y contrataciones de la unidad de gestión educativa local de Ucayali-Contamana, 2024 - Vásquez Arbildo, Wendolin (2025)
This study assesses the effectiveness of the Annual Procurement Plan (PAC) in the acquisitions and contracts of the Local Educational Management Unit of Ucayali-Contamana. The central problem examines how the PAC contributes to the effectiveness of these processes. The objectives are to determine the level of PAC compliance, its efficiency in acquisitions and contracts, and to analyze the impact of its planning, content, approval, publication, and monitoring. A descriptive correlational design with a quantitative methodology and a non-experimental cross-sectional design were employed. The methodology included document analysis and employee interviews. Results show that the PAC significantly improves efficiency in acquisitions and contracts, validating both the general hypothesis and specific hypotheses regarding compliance and effectiveness. It is concluded that comprehensive and well-structured PAC management is crucial for optimizing these processes. The research suggests extending the study to different contexts and developing training programs to enhance PAC management.